Critical Review of M-Learning in Total Quality Management Classroom Practice in an Indonesian Private University - Bunyamin, Bunyamin; Umam, Khoerul; Lismawati, Lismawati (International Journal of Interactive Mobile Technologies (iJIM), 2020)
The widespread use of mobile phones has changed learning practices in the classroom. Many studies have already recommended the advantages of using mobile phones to teach religious education to university students. However, there is a lack of evidence for these advantages in the context of religious education. This research aims to test the effectiveness of M-learning’s utilization in educational programmes for Islamic religion teachers in a private university in Jakarta. A total of 41 pre-service teachers participated in this research. Various methods of data collection are used, including observation, written journals, students’ responses, and tests. Subsequently, the data are analysed utilizing both quantitative and qualitative methods. The findings show that M-learning encourages students’ awareness of conducting independent learning, creates a very interactive discussion atmosphere in class, and improves students’ communication skills in the learning process. However, numerous technical challenges are found in the implementation of M-learning, such as regarding skill in using applications, internet access, and essay tests. The findings of this research offer recommendations to fellow educators regarding using this as an alternative solution.